Neuroprotective effect of geraniol and curcumin in an acrylamide model of neurotoxicity in Drosophila melanogaster: Relevance to neuropathy. - Prasad, S.N.; Muralidhara (Journal of Insect Physiology, 2014)
Chronic exposure of acrylamide (ACR) leads to neuronal damage in both experimental animals and humans. The primary focus of this study was to assess the ameliorative effect of geraniol, (a natural monoterpene) against ACR-induced oxidative stress, mitochondrial dysfunction and neurotoxicity in a Drosophila model and compare its efficacy to that of curcumin, a spice active principle with pleiotropic biological activity. Adult male flies (8-10 days) were exposed (7 days) to ACR (5 mM) with or without geraniol and curcumin (5-10 ?M) in the medium. Both phytoconstituents significantly reduced the incidence of ACR-induced mortality, rescued the locomotor phenotype and alleviated the enhanced levels of oxidative stress markers in head/body regions. The levels of reduced glutathione (GSH) and total thiols (TSH) resulting from ACR exposure was also restored with concomitant elevation in the activities of detoxifying enzymes. Interestingly, ACR induced mitochondrial dysfunctions (MTT reduction, activities of SDH and citrate synthase enzymes) were alleviated by both phytoconstituents. While ACR elevated the activity of acetylcholinesterase in head/body regions, marked diminution in enzyme activity ensued with co-exposure to phytoconstituents suggesting their potency to mitigate cholinergic function. Furthermore, phytoconstituents also restored the dopamine levels in head/body regions. The neuroprotective effect of geraniol was comparable to curcumin in terms of phenotypic and biochemical markers. Based on our evidences in fly model we hypothesise that geraniol possess significant neuromodulatory propensity and may be exploited for therapeutic application in human pathophysiology associated with neuropathy. However, the precise mechanism/s by which geraniol offers neuroprotection needs to be investigated in appropriate neuronal cell models.